The Role of Virtual Reality Exposure Therapy in Anxiety Disorders and Its Impact on Quality of Life: A Literature Review - Kot, Jakub; Zjawiony, Julia; Leja, Wiktoria; Błaszczak, Maciej; Zulfiqar, Zeeshan; Latalska, Katarzyna; Szczupaj, Maciej; Pastuszak, Andżelika; Borkowski, Konrad; Rudnicki, Jakub (Quality in Sport, 2026)
Background. Among the most common mental illnesses in the world, anxiety disorders are linked to severe impairments in everyday functioning and quality of life. The gold standard for treatment is still exposure-based cognitive behavioral therapy (CBT), but it is frequently constrained by psychological and practical obstacles associated with real- life exposure. Aim. This literature review aims to evaluate the effectiveness, mechanisms of action, and clinical applications of virtual reality exposure therapy (VRET) in the treatment of anxiety disorders. Materials and methods. A narrative literature review was conducted using PubMed, Scopus, Web of Science, and Google Scholar. The search included studies published between 2015 and 2026 that examined the use of VRET in clinical populations with anxiety disorders. Randomized controlled trials, observational studies, and systematic reviews were all included. Results. Results show VRET works well for various anxiety conditions - fear of heights, social situations, trauma responses. Unlike real-life exposure, it matches results yet gives more precision, comfort, fewer risks. New tech upgrades make simulations feel closer to reality, easier to reach. Conclusions. The use of virtual reality exposure therapy (VRET) for the treatment of anxietydisorders is still developing and research has shown that it can be an effective and a more accessible form of treatment than other traditional methods. There are some limitations to date such as differing types of studies conducted with some providing no longitudinal data, but further exploration is needed to provide more consistent methodology and standards for evaluating long-term efficacy.